PERFORMANCE OF PLANT GROWTH REGULATORS IN SUNFLOWER GROWING TECHNOLOGY UNDER THE CONDITIONS OF GLOBAL CLIMATE CHANGE - Laslo, O. (Scientific Progress & Innovations, 2022)
Numerous studies of agronomic practice regarding the impact of plant growth regulators on the productivity of oilseeds, in particular sunflowers, contribute to a new search for ways and rates of application to increase seed productivity. Studies on this issue highlight the advantages and disadvantages of drugs used for the pre-sowing treatment of sunflower seeds. Disadvantages of growth regulators include the inhibition of action and reduction of phytotoxic effect on weeds. The advantages of using pre-sowing treatment with biological regulators of sunflower plant growth are much greater, as evidenced by numerous research results on this issue, among which the main ones are the increase in crop productivity. The article presents the features of the influence of biological growth regulators Polymixobacteryn, Phosphoenteryn and Vympel-K on the productivity of sunflower hybrids Bosfora and Estrada. The effectiveness of the drugs varied depending on the characteristics of their active substance, but the most significant was the effect of sunflower seed treatment with biological growth regulator Vympel-K, with the weight of 1000 seeds increased by 15 %, seed weight from the basket by 20 %, yield increased by 14 %. The use of Polymixobacteryn in variant 2 of the regulator in seed treatment contributed to an improvement of 10 %; 9 %; 9 %. The use of Phosphoenteryn for seed treatment resulted in an increase of 13%; 19%; 12% compared with the control. However, there was a decrease in biometrics for all growth regulators on the Bosfora hybrid compared to the Estrada hybrid. Thus, the area of plant leaves in the variant with the use of the drug Vympel- K on the Bosfora hybrid was lower by 17 %, and the dry weight of plants by 49 % compared to the hybrid Estrada. The use of growth regulators for the pre-sowing treatment of sunflower seeds has made it possible to show the potential of hybrids, namely Estrada, which has revealed its genetic potential through the use of new generation plant growth stimulants, as evidenced by increased crop yields and productivity.